Factors influencing housing purchase decisions of millennials in Malaysia - Au, Antony Chee Hoe (2023)
Millennials nowadays are just going into their young adulthood stages where some are just out of university and there are those who are already into their late 30s who are already deep into adulthood. The increasing pressure to own a property and to start families has never been prevalent. Many millennials have thought of owning a home to build a family with but with the increasing prices of property and the aspect of location and even the financial situation, as a property isn’t some small object that is cheap to own and is a long-term financial commitment, me and many other millennials have found it a struggle to move out. With the many policies provided by the government for home ownership, these policies could also be analysed to see how the population, especially Millennials, are being targeted and see if people even know of these policies when deciding on a house. In this research paper, the five main factors that would influence the decision-making process of purchasing a house are location, financial, property developer, structural, and family member influence in that order. The questionnaire focused on all five factors which had 80 respondents. Majority of respondents ranked financial as the top for its influence in housing purchase decisions followed by location, structural, property developer and lastly, family member influence. The results of the research could help potential property developers, investors, and government officials in their planning of properties for the future of the growing population of Malaysia and can try to solve the property overhang problem.